2015
DOI: 10.1515/bj-2015-0005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Variables on Recovery Time in Patients Receiving Hemodialysis

Abstract: Introduction.Patients on hemodialysis (HD) are proven to have impaired Health Related Quality of Life (HRQoL) compared to the general population. Recovery from the hemodialysis session is a permanent problem among majority of patients receiving HD treatment. A partial explanation may be the osmotic imbalance between different compartments of the body due to the fluid and electrolyte movement across the cell membrane which is a part of the HD process itself. The aim of our study was to see whether the length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
3
1
0
3
Order By: Relevance
“…Some studies reported correlations between a few biochemical or hematological factors and recovery time [25,26]. However, other studies reported no significant relationship between Kt/V, URR, and albumin, creatinine, calcium, and Hb levels with recovery time, which was similar to our findings [7,8,27,28]. We found that the Kt/V, URR, and Hb values of most participants (Kt/V ≥ 1.4, URR ≥70%, and Hb level ≥ 11 g/ dL were found in 65.5%, 60.5%, and 54.7% of the participants respectively of the participants respectively) were within the recommended limits posted in the guidelines [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies reported correlations between a few biochemical or hematological factors and recovery time [25,26]. However, other studies reported no significant relationship between Kt/V, URR, and albumin, creatinine, calcium, and Hb levels with recovery time, which was similar to our findings [7,8,27,28]. We found that the Kt/V, URR, and Hb values of most participants (Kt/V ≥ 1.4, URR ≥70%, and Hb level ≥ 11 g/ dL were found in 65.5%, 60.5%, and 54.7% of the participants respectively of the participants respectively) were within the recommended limits posted in the guidelines [29,30].…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated that malnutrition was associated with a prolonged DRT. We found a significant negative correlation between serum albumin level and the DRT (rs = − 0.143, p = 0.048), which is similar to the findings of Smokovska et al [32] who reported that a shorter DRT was associated with a higher serum albumin level. On the other hand, Bossola et al [6] found no significant correlation between serum albumin level and the DRT; however, they explained this by stating that all cases were managed till target albumin levels according to the KDOQI guidelines.…”
Section: Discussionsupporting
confidence: 91%
“…We found a negative significant correlation between the DRT and age (rs = − 0.179, p = 0.013), which is in line with the findings of Fitzpatrick et al [33] and Yoowannakul et al [34]. Other studies revealed no association between these variables [14,32,35,36]. It is possible that the shorter recovery durations recorded by elderly individuals are associated with patients' greater satisfaction and lower expectations despite having poorer clinical profiles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Terdapat beberapa studi yang menemukan bahwa kadar serum albumin dapat mempengaruhi waktu pulih pascahemodialisis (Hussein et al, 2017;Rayner et al, 2014). Parameter biokimia lain yang juga dapat mempengaruhi waktu pulih adalah kadar ureum serum (r = -0,309; p = 0,003), kadar hemoglobin (r = -0,412; p = 0,0001) dan PCR (r = -0,241; p = 0,017) (Smokovska, Grozdanovski, & Spasovski, 2015). Lebih lanjut, hemoglobin ditemukan sebagai prediktor dominan terhadap waktu pulih pascahemodialisis.…”
Section: Faktor Biokimiaunclassified